2023
DOI: 10.1007/s13679-023-00510-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Peripheral Artery Disease: Current Evidence and Controversies

Abstract: Purpose of Review Obesity is a significant public health problem and a major risk factor for the development and progression of atherosclerosis and its cardiovascular manifestations. Lower extremity peripheral artery disease (PAD) affects 3%–10% of the Western population and, if left untreated, can lead to devastating outcomes with both an increased risk of morbidity and mortality. Interestingly, the association between obesity and PAD remains debatable. Whereas it is well known that PAD and obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 150 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…We studied baseline rather than the mean BMI during the study period in order to minimise the possibility of reverse causality, namely that cardiac disease or malignancy leads to weight loss. The association of a higher BMI with lower cardiovascular [ 39 42 ] and cancer [ 43 45 ] mortality has been previously reported and is often referred to as the obesity paradox. The reasons for this are unclear, given the known association of adiposity with adverse outcomes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We studied baseline rather than the mean BMI during the study period in order to minimise the possibility of reverse causality, namely that cardiac disease or malignancy leads to weight loss. The association of a higher BMI with lower cardiovascular [ 39 42 ] and cancer [ 43 45 ] mortality has been previously reported and is often referred to as the obesity paradox. The reasons for this are unclear, given the known association of adiposity with adverse outcomes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have uncovered a potential positive correlation between obesity and PAD. However, some studies have also raised the concept of the “obesity paradox” ( 6 ), which has spurred researchers to seek more evidence in order to establish a causal relationship between the two. An MR study conducted within the UK Biobank, involving 367,703 participants, has indicated that a higher BMI, particularly with a focus on the fat mass index, is associated with an elevated risk of several cardiovascular diseases, including PAD ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier systematic study conducted among Hispanics found that despite a higher prevalence of risk factors such as hypertension, obesity, and diabetes when compared to non-Hispanic whites, Hispanics displayed notably lower rates of PAD and carotid artery disease, suggesting the existence of an “obesity paradox” within the Hispanic population ( 29 ). Simultaneously, multiple studies have suggested that individuals of African descent might exhibit a heightened susceptibility to PAD ( 1 , 6 , 30 , 31 ). These findings imply the presence of racial disparities in the causal relationship between obesity and PAD, emphasizing the significance of studying diverse ethnic groups in our future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both COVID-19 and obesity are influenced by the same pre-existing health conditions and risk factors, such as an advanced age, a deteriorated socio-economic status and co-existing health conditions ( 2 , 11-15 ). Comorbidities, such as type 2 diabetes mellitus and cardiovascular disorders, as well as cancer, are typically the result of obesity, which contribute to unfavorable COVID-19 outcomes ( 2 , 16-20 ). Additionally, obesity influences the immune system, which has implications in the body's ability to defend against infections and, perhaps, the COVID-19 outcomes ( 20-22 ).…”
Section: The Interconnectedness Of Covid-19 and Obesitymentioning
confidence: 99%